2004
DOI: 10.1161/01.cir.0000128598.72920.b5
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin Is an Independent Risk Factor Predicting Death in Male Patients With End-Stage Kidney Disease

Abstract: Background-Patients with end-stage kidney disease (ESKD) have a reduced life expectancy mainly as the result of cardiovascular diseases. Relaxin has been implicated in the pathogenesis of cardiovascular diseases. We analyzed the impact of relaxin on death in patients with ESKD. Methods and Results-Patients (n ϭ245; 122 women, 123 men) on long-term hemodialysis were followed for 1140 days for death. Blood samples for analysis of relaxin, C-reactive protein, Troponin T, cholesterol, HDL, brain natriuretic peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…From the initial cohort of 245 prevalent patients [28][29][30] , 230 plasma probes were available for the current study. These 230 patients on maintenance haemodialysis were followed prospectively for 52 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the initial cohort of 245 prevalent patients [28][29][30] , 230 plasma probes were available for the current study. These 230 patients on maintenance haemodialysis were followed prospectively for 52 months.…”
Section: Resultsmentioning
confidence: 99%
“…The cohort was recruited in March 2000 from 2 dialysis centres in Berlin, Germany, as previously described [28,29] . The facilities are non-proprietary units of the Kuratorium für Heimdialyse (KfH, Neu-Isenburg, Germany), a unique non-profit facility.…”
Section: Study Populationmentioning
confidence: 99%
“…From the initial cohort of 245 prevalent patients (16,17), 232 plasma probes were available for the current study. These 232 patients who were on maintenance hemodialysis were followed prospectively for 52 mo.…”
Section: Resultsmentioning
confidence: 99%
“…The initial documentation (and the work by Hocher et al [16,17]) included age, gender, underlying renal disease, residual renal function and urinary output, presence of diabetes, hypertension (diagnostic criteria: need for any antihypertensive drug and/or elevated baseline BP), smoking, and presence of coronary heart disease (patients with a history of myocardial infarction, coronary heart disease confirmed by coronary angiograms, or typical stable angina confirmed by stress echocardiography or radionuclide studies). Blood samples were taken from all studied patients during March 2000, immediately before dialysis.…”
Section: Study Populationmentioning
confidence: 99%
“…83 Interestingly, it has been reported that relaxin is released from the failing heart, producing circulating levels that can approach those reached during pregnancy, although the role played by cardiac-produced relaxin is unclear. [84][85][86][87][88][89][90] However, there are concerns about the lack of validation of the assay used for these studies, and therefore further study is needed to prove that relaxin is produced by the heart. 72 In addition to the heart, relaxin protects against ischemia-reperfusion injury in other organs including kidney, lung, liver, brain, and intestine.…”
mentioning
confidence: 99%